Selected Properties and Microstructure of Concrete with Tire Rubber Granulate as Recycled Material in Construction Industry - Marcalikova Zuzana; Gandel Radoslav; Jerabek Jan; Varak Jaromir (Civil and Environmental Engineering)
The paper explores the use of recycled materials in the construction industry to promote sustainable development. There is a growing demand for recycling and innovative materials in engineering. The study specifically investigates the potential of tire rubber recyclate as a recycled raw material, comparing two different mixtures in an experimental program. These mixtures highlight the importance of utilizing local resources, aligning with the principles of the circular economy. The experimental program focuses on evaluation of mechanical properties in addition to specialized tests. Findings indicate that higher proportions of rubber granulate not only impact mechanical properties but also significantly affect durability when exposed to environmental factors.